GATE 2020 Electronics and Communication Engineering:previous year solved questions (1991-2019 ) - Kreatryx (KREATRYX Pub., 2019)
GATE 2020 Electronics and Communication Engineering:previous year solved questions (1991-2019 ) / Kreatryx. -- New Delhi: KREATRYX Pub., 2019